Electrochemical uptake/release of lithium in GaNb11O29 nanowires as anode material for rechargeable lithium ion battery. Issue 12 (15th August 2020) - Wang, Zhen; Zheng, Runtian; Li, Yuhang; Yu, Haoxiang; Liu, Tingting; Peng, Na; Zhang, Jundong; Shui, Miao; Shu, Jie
Abstract: Nowadays, it is of great urgency to research for appropriate materials to construct high-performance lithium-ion batteries (LIBs) because of the growth of social demand. Among them, niobium type metal oxides are potential candidates for anode materials. Here, we propose GaNb11 O29 with shear-ReO3 crystal structure as anode material. It is an intercalation-type material with high theoretical capacity and safe working voltage. In this work, GaNb11 O29 nanowires are synthesized by electrospinning. The nanostructure design can effectively improve lithium storage behavior. Accordingly, GaNb11 O29 nanowires provide a high reversible capacity (233.4 mAh g -1 at 100 mA g -1 ), outstanding rate capability (168.8 mAh g -1 at 700 mA g -1 ) and superior long-term stability (0.031% capacity loss per cycle after 500 cycles). Furthermore, the kinetic analysis confirms the pseudocapacitive contribution during cycling, which contributes to the rapid Li-storage. In addition, in-situ XRD characterization is conducted to further unveil the Li-storage mechanism in lithiation/delithiation processes. This work suggests that GaNb11 O29 nanowires are potential anode material for rechargeable batteries, which enriches the choice for high-performance LIBs.